Modeling, Simulation, and Control for a Continuous Flowporous Media Burner - Cubillos-Montecino, F; Henriquez-Vargas, L; Bubnovich, V; Donoso-Garcia, P (2013)
The filtration combustion (FC) system in inert porous matrix is one of the most efficient combustion systems due to its better thermal efficiency and lower pollutant formation. The principal drawback of a uniform FC is its transient condition because the combustion wave can propagate freely along the porous matrix in either the downstream or upstream direction. In the present paper we study the positioning of the combustion front in a uniform FC by using a model predictive control (MPC) scheme. The study was carried out by means of simulations considering as manipulated variables the gas filtration velocity and fuel equivalence ratio of CH4/air gas mixtures. The controlled variable was the flame position along the burner. Confinement schemes for combustion wave position are introduced in two configurations: set-point tracking and periodically reversible operation, which show a powerful control scheme able to permanently operate and optimize homogeneous FC burners. © 2013 by Begell House, Inc.